The usage of Instagram app on the example of young consumers of the Generation Z - Olejniczak, Aneta (Serbian Journal of Management, 2022)
The popularity of social media continues to grow. Many statistics report that mostly young people spend the highest amount of time on social networking sites. The purpose of the paper is to present results of the study on respondents’ browsing and content publishing behavior on the Instagram platform. The author focused on several available forms, such as posts, stories, IGTV, live. The study focused on young consumers, belonging to generation Z. The author mainly researched how much time does the young generation spend on Instagram platform, which form is more preferred among respondents, in context of viewing or creating content by them. Moreover the study also focused on differences in the use of Instagram app among generation Z based on gender, education and place of residence. The study showed that the representatives of the mentioned generation prefer both viewing and adding primarily stories, and secondarily posts. Neither IGTV nor live are of much interest. Recipients are reluctant to view or create this type of content.
Keywords: young consumers; young creators; generation Z; social media; Instagram